Sentiment Analysis of Jokowi’s Candidate Discourse in Three Periods using the Naïve Bayes Method - Dita Nurmadewi; Mia Amaliah; Hajar Hanifah; Ulfa Bunayya Purwanti; Maruti Sekar Arum; Nanang Wijaya Kusuma; Sri Yuniati (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
Approaching the 2024 presidential election many discourses develop among the public regarding the presidential election period which takes place every five years. One of the most widely discussed political discourses is the candidacy of President Jokowi for the third term of his leadership. This study aims to carry out a sentiment analysis of the public on the discourse. The sample data for sentiment analysis is taken from Twitter social media in the form of tweet status. The stages carried out by the researchers began with determining the research method through text mining and sentiment analysis using the Naive Bayes algorithm. The results of the research conducted revealed that there are still many positive sentiments compared to negative sentiments related to the discourse of Jokowi's candidacy in the three periods. Keywords: Sentiment Analysis, Naive Bayes, Twitter, Jokowi.